Risk factors of developing inflammatory bowel diseases - Aleksandra Iwona Zimna; Hubert Wróblewski; Dariusz Chojęta; Ewelina Zygmunt; Anna Kozłowska (Kazimierz Wielki University, 2022)
Introduction: The pathogenesis of inflammatory bowel disease (IBD) is still unknown. It is known to be multi-factorial. The world is seeing an ever increasing number of new cases of these diseases. Ulcerative colitis and Crohn's disease are the main representatives of inflammatory bowel diseases. Aim: The aim of the study was to analyze risk factors for inflammatory bowel diseases. Materials and methods: The results were obtained on the basis of a questionnaire survey. Results: 95 people took part in the survey aged 16 to 72 years old. 35.8% were men and 64.2% were women. 78% lives in cites, only 22% are rural residents.  56.4% of them suffer from ulcerative colitis and 43.6% from Crohn's disease. 40.4% of respondents smoked cigarettes in the past, but currently only 12.6% are still struggling with the addiction. Only 4 people declare brushing their teeth after each meal. 18 people confirm the presence of NCDH in their families, 19 suffer from other autoimmune diseases at the same time. 2 people from among the respondents - also celiac disease. One person had Salmonella and Shigella infection.  Conclusions: Due to the mutual cause-effect relationships between genetic predisposition and the influence of environmental factors, it is currently difficult to state which of the above factors plays a decisive role. Environmental factors that play a role in the etiopathogenesis of IBD include, first and foremost, the intestinal bacterial flora, diet, human environment and smoking. There is a clear tendency for the coexistence of autoimmune diseases in the group of patients with NCJ and a predisposition to the disease in the family. There is also a need to educate patients about the benefits of taking probiotics and taking care of proper eating habits. Key words: inflammatory bowel diseases, risk of developing the disease, irresponsible patient